1995
DOI: 10.1128/cdli.2.1.14-17.1995
|View full text |Cite
|
Sign up to set email alerts
|

Serum antibody response to proteins of Moraxella (Branhamella) catarrhalis in patients with lower respiratory tract infection

Abstract: We searched for antibodies against Moraxella (Branhamella) catarrhalis proteins in the sera of patients with lower respiratory tract infection. Sera from 48 patients with M. catarrhalis and 39 patients without M. catarrhalis in their lower respiratory tract specimens were studied by a gel electrophoresis-immunoperoxidase technique; sera from 23 healthy adult blood donors were also included. Immunoglobulin G (IgG) antibodies against a 28-kDa protein were found significantly more frequently in patients with M. c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In spite of this limitation, the prospective design of this study allows us to measure antibodies made specifically to each episode of acquisition of M. catarrhalis because of the availability of prospectively collected preacquisition and postclearance samples. Christensen et al (1995Christensen et al ( , 1996 identified a serum IgG response to an OMP in the 28-kDa range in adults with lower respiratory tract infections with M. catarrhalis. This 28-kDa protein might be OMP G1b.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this limitation, the prospective design of this study allows us to measure antibodies made specifically to each episode of acquisition of M. catarrhalis because of the availability of prospectively collected preacquisition and postclearance samples. Christensen et al (1995Christensen et al ( , 1996 identified a serum IgG response to an OMP in the 28-kDa range in adults with lower respiratory tract infections with M. catarrhalis. This 28-kDa protein might be OMP G1b.…”
Section: Discussionmentioning
confidence: 99%
“…This epitope is present in all disease-associated isolates of M. catarrhalis tested to date and induces the synthesis of antibodies that, when used to passively immunize mice, enhanced the elimination of M. catarrhalis in a pulmonary clearance model (27). Equally important, the very high molecular weight UspA antigen composed of UspA1 and UspA2 has been shown to be a target for antibodies present in convalescent sera of patients recovering from M. catarrhalis infections (13,25,27), indicating that one or both of these proteins are expressed in vivo.…”
mentioning
confidence: 99%
“…Second, children develop serum antibodies to M. catarrhalis after age 4 (14), and this appears to correlate with a decrease in the frequency of otitis media caused by M. catarrhalis. Third, antibodies to M. catarrhalis antigens have been detected in both the acute-phase and convalescent-phase sera of adult patients (7,15). These data suggest that an appropriate humoral response to the surface antigens of this bacterium is likely to provide protection.…”
mentioning
confidence: 89%
“…Passive immunization with one of these MAbs, 17C7, enhanced pulmonary clearance of both homologous and heterologous isolates in a murine pulmonary challenge model (17). The observation that human convalescent-phase sera contain antibodies to UspA indicates that this protein is expressed by M. catarrhalis in vivo (7,15,17). M. catarrhalis gains entry to the host by attachment to and colonization on the epithelial cell surface of the respiratory tract (1,2).…”
mentioning
confidence: 99%